Adult-Onset Still's Disease and cytomegalovirus infection - Bento, DP (2017)
We present a case of a previously asymptomatic 34-year-old man that presented to the emergency department with two weeks of fever, arthralgia of the wrists and knees and sore throat. He was diagnosed with cytomegalovirus (CMV) mononucleosis. The patient remained symptomatic in the 5 following months. After an extensive workup to exclude other clinical conditions, a liver biopsy was performed and CMV hepatitis was diagnosed. He started valganciclovir therapy. Approximately one year after the initial complaints, the patient remained ill and presented clinical criteria compatible with Adult Onset Still's Disease. The patient had a marked improvement after institution of prednisolone, an effect that has been sustained during the following months.